THE RELATIONSHIP BETWEEN SELF-COMPASSION AND INCREASED BLOOD PRESSURE IN LATE ADULTS OF KAYE LEE VILLAGE, INGIN JAYA DISTRICT, ACEH BESAR - Mardhatillah Mardhatillah; Eridha Putra; Erma Yanti (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Hypertension is a factor that causes serious illnesses such as heart attacks, kidney failure, and strokes. The research design used was descriptive analytic with research subjects in late adults aged 36-45 in Kaye Lee Village, Ingin Jaya District, Aceh Besar. The sampling technique used Total Sampling with a total of 35 respondents. The results of this study indicate a significant p-value (0.062 <0.05). Based on the results of the above study, it can be concluded that there is a significant relationship between self-compassion and increased blood pressure in late adulthood in Kaye Lee Village, Ingin Jaya District, and Aceh Besar. Adults aged 35 and over are very productive with various activities. It's no wonder that at that age they work and have almost no free time to rest. Most of the time is spent at work, resulting in them not being able to prepare their food at home, so they often buy ready-to-eat food, either buying it directly or ordering it online, the habit of consuming ready-to-eat food is done more than 2 times a week so they in the last 6 months often experience complaints of headaches and dizziness.